2021
DOI: 10.1371/journal.pntd.0009786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating livestock farmers knowledge, beliefs, and management of arboviral diseases in Kenya: A multivariate fractional probit approach

Abstract: Globally, arthropod-borne virus (arbovirus) infections continue to pose substantial threats to public health and economic development, especially in developing countries. In Kenya, although arboviral diseases (ADs) are largely endemic, little is known about the factors influencing livestock farmers’ knowledge, beliefs, and management (KBM) of the three major ADs: Rift Valley fever (RVF), dengue fever and chikungunya fever. This study evaluates the drivers of livestock farmers’ KBM of ADs from a sample of 629 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
3
9
1
Order By: Relevance
“…Knowing clinical signs and symptoms is crucial for detection of the disease at an early stage in order seek treatment before the situation worsens. This was consistent with the other studies (39,40) that reported the importance of farmers knowledge in early detection of the diseases on the farm. Conversely, lack of adequate knowledge of diseases is one of the main contributors to the vicious cycle of endemic diseases in animals and humans prevalent in poor rural communities in Africa (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Knowing clinical signs and symptoms is crucial for detection of the disease at an early stage in order seek treatment before the situation worsens. This was consistent with the other studies (39,40) that reported the importance of farmers knowledge in early detection of the diseases on the farm. Conversely, lack of adequate knowledge of diseases is one of the main contributors to the vicious cycle of endemic diseases in animals and humans prevalent in poor rural communities in Africa (41,42).…”
Section: Discussionsupporting
confidence: 93%
“…Education level higher than primary school was associated with better knowledge on RVF mainly because education gives one the ability to easily comprehend information about a disease [50,51]. The relationship between education level and knowledge of RVF has been reported before in Baringo [20] and Isiolo Counties [22]. A higher socio-economic index, reflecting the wealth status of a household, was associated with better knowledge and a positive attitude to RVF because wealthy households are most likely to have more access to information on diseases and their prevention and can afford to manage the disease [20,31].…”
Section: Plos Global Public Healthmentioning
confidence: 57%
“…Most of the education on RVF has not emphasized on this important aspect of the epidemiology of the disease as much as the Anopheles mosquito in malaria transmission. Low level of knowledge on the role of mosquitoes in RVF epidemiology has been evident in previous studies in Kenya [20,21], Uganda [37], Malawi [39] and Tanzania [10]. Knowledge of risk factors for RVF generally leads to avoidance behavior and preparedness during outbreaks.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This health promotion deficit has resulted in poor knowledge, attitude, and practices amongst the general populace in affected countries. In addition, the lack of public trust in the appropriate treatment options offered by healthcare services has contributed to the spread of arboviral diseases in Africa [61][62][63][64].…”
Section: Challenges In Addressing the Risk Of Arboviruses In Africamentioning
confidence: 99%